Does Freedom of Association Justify Restrictions on Immigration? - Vinx, Lars (Res Cogitans, 2015)
Christopher Wellman has argued that legitimate states enjoy a right to freedom of association that necessarily includes a right to exclude immigrants. This paper shows that Wellman’s argument for this conclusion is unsound since it is based on a construction of collective rights that is inapplicable to the rights of a state.